2014
DOI: 10.1016/j.ejvs.2014.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Delayed Sealing in Selected Patients with a Primary Type-Ia Endoleak After Endovascular Aneurysm Repair

Abstract: All but one of the primary type-Ia endoleaks sealed spontaneously. Until sealing, the risk of rupture persisted, but subsequently only one recurrence of type-Ia endoleak was seen. In selected patients, a conservative approach for primary type-Ia endoleaks may be justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 19 publications
(17 reference statements)
3
30
0
Order By: Relevance
“…Similar results have been seen in several small series in which >50% of persistent type IA endoleaks have resolved by the first follow-up CT scan. 7,8,10,13 With longer follow-up, only 14% of the endoleaks present at the case end were still present at 1 year. More important, there was no difference in overall survival in those patients who left the operating room with a persistent endoleak compared with those whose endoleaks resolved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results have been seen in several small series in which >50% of persistent type IA endoleaks have resolved by the first follow-up CT scan. 7,8,10,13 With longer follow-up, only 14% of the endoleaks present at the case end were still present at 1 year. More important, there was no difference in overall survival in those patients who left the operating room with a persistent endoleak compared with those whose endoleaks resolved.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggest that type IA endoleaks may not carry such a dire prognosis as previously believed. Several studies have demonstrated low rates of rupture and aneurysm-related mortality and high rates of spontaneous sealing in select patients, [8][9][10][11][12][13][14] but these studies are limited by small numbers and limited follow-up. The goal of this study was to examine our institutional experience with type IA endoleaks in an effort to document long-term outcomes.…”
mentioning
confidence: 99%
“…1,2 While intraoperative type Ia endoleaks can resolve spontaneously in some cases, justifying a watchful waiting strategy, late type Ia endoleaks need to be treated because they are strictly associated with sac growth, and ultimately, to aneurysm rupture. [14][15][16] At the moment there is no consensus about the optimal treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In an evaluation of 15 patients, Bastos and colleagues 30 identified 14 patients who had spontaneous type Ia endoleak closures, with 1 patient ultimately developing a recurrent type Ia endoleak years later, and 1 patient with an unconfirmed recurrent endoleak. Kim and coworkers 18 evaluated 86 patients undergoing EVAR and found spontaneous closure of type Ia endoleaks in 7 of 10 patients, although the median follow-up period was only 14 months.…”
Section: Discussionmentioning
confidence: 99%